Apramycin for the early-weaned pig - Jim L Nelssen; G L Allee; R C Thaler; W H Turlington (Kansas Agricultural Experiment Station Research Reports, 1987)
A total of 108 21-day-old pigs, weighing less than 10 lb, were utilized in two, 28-day trials to compare the effects of feeding high nutrient-density diets with either added apramycin, neomycin, or carbadox on pig performance. In Tria1, pigs fed the diet containing ApralanÂ® gained slightly faster and were more efficient (P<.05) than pigs fed neomycin during the first 14 days postweaning. There were no differences in pig performance in Trials I or II for the entire 28-day period. Two additional 28-day on-farm studies using a total of 427, 21-day old pigs were conducted, feeding a high nutrient-density diet medicated with either apramycin or neomycin plus terramycin. In both on-farm trials, pigs fed apramycin gained faster (P<.05) than pigs fed neomycin plus terramycin for the initial 14 days post weaning. In the second on-farm trial, feed intake was higher (P<.09) during the first 14 days for pigs fed apramycin. Additionally, pigs fed diets medicated with apramycin were slightly heavier (1. 7 and 1.5 additional pounds for the first and second on-farm trials, respectively) at 28 days post weaning compared to pigs fed neomycin plus terramycin. These results indicate that apramycin will improve the performance of early-weaned pigs fed high nutrient-density diets compared to other feed medications.; Swine Day, Manhattan, KS, November 19, 1987
Keywords: Swine day; 1987; Kansas Agricultural Experiment Station contribution; no. 88-125-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 528; Swine; Apramycin; Early-weaned pig